Cell senescence in neuropathology: A focus on neurodegeneration and tumours. (1st February 2021) - Carreno, Gabriela; Guiho, Romain; Martinez‐Barbera, Juan Pedro
Abstract: The study of cell senescence is a burgeoning field. Senescent cells can modify the cellular microenvironment through the secretion of a plethora of biologically active products referred to as the senescence‐associated secretory phenotype (SASP). The consequences of these paracrine signals can be either beneficial for tissue homeostasis, if senescent cells are properly cleared and SASP activation is transient, or result in organ dysfunction, when senescent cells accumulate within the tissues and SASP activation is persistent. Several studies have provided evidence for the role of senescence and SASP in promoting age‐related diseases or driving organismal ageing. The hype about senescence has been further amplified by the fact that a group of drugs, named senolytics, have been used to successfully ameliorate the burden of age‐related diseases and increase health and life span in mice. Ablation of senescent cells in the brain prevents disease progression and improves cognition in murine models of neurodegenerative conditions. The role of senescence in cancer has been more thoroughly investigated, and it is now accepted that senescence is a double‐edged sword that can paradoxically prevent or promote tumourigenesis in a context‐dependent manner. In addition, senescence induction followed by senolytic treatment is starting to emerge as a novel therapeutic avenue that could improve current anti‐cancer therapies and reduce tumour recurrence. In this review, we discuss recent findings supporting the role of cell senescence in the pathogenesis of neurodegenerative diseases and in brain tumours. A better understanding of senescence is likely to result in the development of novel and efficacious anti‐senescence therapies against these brain pathologies. Abstract : This review discusses the role of senescent cells in brain pathologies, in particular age‐associated neurodegenerative diseases such as Alzheimer's disease, Parkinson's disease and multiple sclerosis, as well as brain tumours, specifically craniopharyngioma, low‐grade glioma, glioblastoma multiforme, medulloblastoma and diffuse midline glioma. We present evidence accumulated from in vitro and in vivo studies in both mice and humans. The translational implications of such studies will also be discussed.